Tribal Development through Watershed Programme-A Case Study - Vohra, P.H. (Journal of Soil and Water Conservation, 2022)
Gujarat State is mostly a dry farmin State and receives low rainfall which is also highly erratic. Tribal communities are mostly on eastern strip with irregular terrain. Watershed development works carried out by Gujarat Land Development •Corporation are in tribal area of Sabarkantha district. Impact of soil and water conservation works after 5 years has been significant. Irrigation commanding three wells has increased between 26 and 91 percent while cropping intensity between 120 and 150 percent. Inconic of a group of 10 farmers has resen by 228 percent.